On the margins: a review of policies and laws in support of farmer-managed seed systems in Africa - Vernooy, Ronnie; Adokorach, Joyce; Kimani, Dominic; Marwa, Anna; Mayoyo, Alfios; Nyadanu, Daniel (2023)
A new review report concludes that seed (related) policies and laws in 14 African countries acknowledge to some degree that farmer-managed seed systems exist, but most of them do not provide concrete support for farmer-managed seed systems. Much remains to be done to promote and support the use of diverse genetic resources for climate change adaptation, e.g., through the strengthening of national and (sub)regional collaboration on integrated seed sector development and more support for farmer-managed seed system activities, such as community seed banking and local seed business development. This brief presents the main findings of the review.